ANALYSIS OF REGIONAL TRADITIONS OF UKRAINIAN EMBROIDERY AND THEIR SEGMENTATION USING DIGITAL TECHNOLOGIES - NADOPTA, TETIANA; YERII, ANDRII; ANDRIEIEVA, OLENA; SKIDAN, VLADYSLAVA; ZUBKO, HANNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper presents the results of the analysis of the reflection of regional traditions in Ukrainian embroidery and their implementation in the modern design of traditional clothing. The question of the transformation of Ukrainian embroidery in the conditions of European integration, globalization and modern requirements is considered. The method of adaptation of Ukrainian traditions in modern design solutions is defined and the tool of their implementation in practical activity is proposed. The process of globalization in Ukraine is an important stage of transformation of political, economic systems and public consciousness. An important aspect of this process is the preservation of cultural heritage, in particular, the art of embroidery, which is an integral part of the national identity of the Slavic peoples. Ukrainian embroidery, based on ancient rites and symbols, reflects the local characteristics of different regions of Ukraine and plays the role of a social code that carries centuries-old traditions that are traced in the process of the evolution of patterns on the embroidery. It has deep historical roots and remains relevant in modern times, performing both decorative and sacred functions. Embroidery has the property of reflecting the peculiarities of the inner world of the individual and the culture of the community, demonstrating values and individualism. In the course of the actualization of the use of embroidery ornaments, the question of a modern technological approach emerges, the choice of materials for embroidery, which have evolved from natural to modern factory threads, is also important, as this important aspect directly affects embroidery technologies and changes classical approaches to pattern design. In the context of European integration and globalization, it is important to preserve and adapt Ukrainian embroidery to modern needs, justifying a method that allows integrating Ukrainian traditions into modern design solutions and defining a new fashion direction in the context of neoclassical Ukrainian traditions. The approach proposed by the authors to the analysis of regional traditions contained in embroidery patterns fully allows one to convey one’s own national motifs by demonstrating the ornaments of vyshyvanka.